Kønsligt hierarki eller religiøs androgyni - Hjort, Birgitte Graakjær (Religionsvidenskabeligt Tidsskrift, 2000)
<p class="MsoNormal" style="margin: 0cm 0cm 0pt; text-align: justify; mso-pagination: widow-orphan; tab-stops: 0cm 14.2pt 28.4pt 42.65pt 56.85pt 71.1pt 85.3pt 99.5pt 113.75pt 127.95pt 142.2pt 156.4pt 170.6pt 184.85pt 199.05pt 213.3pt 227.5pt 241.7pt 255.95pt 270.15pt 284.4pt 298.6pt 312.8pt 327.05pt;">Only a few texts from the New Testament have been used and misused as have 1 Cor 11:2-16. A widespread misreading of the pericope consists in the interpretation that Paul there argued against equality between men and women generally or in the context of worship. The purpose of this article is twofold: To demonstrate why this reading is untenable and to argue for a more proper interpretation. <p class="MsoNormal" style="margin: 0cm 0cm 0pt; text-indent: 14.2pt; text-align: justify; mso-pagination: widow-orphan; tab-stops: 0cm 14.2pt 28.4pt 42.65pt 56.85pt 71.1pt 85.3pt 99.5pt 113.75pt 127.95pt 142.2pt 156.4pt 170.6pt 184.85pt 199.05pt 213.3pt 227.5pt 241.7pt 255.95pt 270.15pt 284.4pt 298.6pt 312.8pt 327.05pt;">My reading is based on Paul’s line of argument, including his remarkable formation of the kephale-structure and the position of the pericope between chapters (8 and) 10 and 11:17-21, respectively, as well as on the letter as a whole. All these things together indicate that the problem under discussion was not the relationship between the sexes as such, but this relationship seen in a religious, ritual context. Paul reproved a conduct whose shamefulness lay in its threat to both the gender polarity according to the creation and the sovereignty of God, a conduct which may also have caused divisions in the community. What Paul was arguing against, was a syncretism whose hallmark was an emancipatory equalization of gender polarity and, maybe, ritual intoxication and whose religious precedent was to be found in the worshipping of idols. With this interpretation as the main criterion for testing different hypotheses put forward to explain the historical situation causing Paul to write the text, I have found that a possible reconstruction consists of an influence on the Corinthians from pre-gnostic thoughts in a broad sense, combined with a more specific influence from the cult of Dionysus.